Student perspectives on their digital footprint in virtual learning environments - Rakow, Katie E.; Upsher, Rebecca J.; Foster, Juliet L. H.; Byrom, Nicola C.; Dommett, Eleanor J. (Frontiers in Education, 2023)
The prevalence of mental distress among young adults, including those at university, has increased. In this context, learning analytics, students' digital trace data, are increasingly being used to understand student mental health. In line with calls for more research on learning analytics from student perspectives, as part of a broader focus group study, 44 undergraduate students from three UK universities were invited to consider how they felt about having a digital footprint on their virtual learning environment (VLE). Two main themes were constructed using reflexive thematic analysis. First, students’ responses depended on the perceived threat to their privacy and identity. Some students were indifferent if no threat was perceived, but expressed unease if there was. Second, some students expressed personal preference for autonomy over use of their VLE data. Two uses identified were for non-judgmental personalized support, and using aggregated data to improve student learning. These themes suggest how the use of educational digital data can, under some circumstances, impact wellbeing negatively. The students’ perspectives garnered from the focus groups could have implications for policy and practice concerning privacy and surveillance, the possibility for misuse or misinterpretation of data, and informed consent. This small study supports the importance of partnering with students to develop and implement guidance for how VLE learning analytics data are used and interpreted by students and staff, including lecturers, to protect and enhance student mental wellbeing.